The habitat, ecological life conditions, and usage characteristics of the otter (Lutra lutra L. 1758) in the Balikdami Wildlife Development Area - Özkazanç, Nuri Kaan; Ozay, Emir; Özel, Halil Barış; Cetin, Mehmet; Sevik, Hakan (Springer Science and Business Media LLC, 2019)
The study was conducted to determine the habitat usage characteristics of the otter, which provides important information on the status of aquatic and coastal ecosystems. The Balikdami (Fish House) Wildlife Development Area, where the study was carried out, was registered in 1994 and was declared a natural site in 1998. The total area of the site is 1470 km2. In order to determine the habitat usage characteristics of the otter, photo traps were placed according to the assumed habitat characteristics between the river and the terrestrial areas near the river. Previous research suggested that there should be at least 15 days of observation. In this study, 11 photo traps were left in the study area at a ratio of 1463 camera traps/day. A total of 37 different otter images were obtained in 3, 4, and 5 points at the end of the study. The data indicated that the otters preferred to use places that were close to the aquatic aquarium. They did not prefer densely vegetated areas, open areas, and places where there was human intervention, large construction, water borders, water pump edges, and areas with high human activity. The otters were active at night. While the number of otters is increasing in Turkey, according to the International Union for Conservation of Nature (IUCN) Red List, otters are in the NT (near threat) category. The otter is protected in all countries where it is increasing in number. Therefore, a better understanding of the habitat preferences of the otter will help us to better protect it.
Keywords: Human Disturbance; Ecology; Turkey; Parks, Recreational; Otter Disturbance; Animals, Wild; Management, Monitoring, Policy and Law; Habitat Structure; Spatial Structure; Rivers; Environmental Influences; Animals; Humans; Protect; Ecosystem; Environmental Restoration and Remediation; Environmental Monitoring; Otters; 15. Life on land; 14. Life underwater